The Relationship between Father's Violent Behavior towards Temperament of Teenager - Sri Yuliani Putri; Jumaini Jumaini; Erna Marni (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2019)
Father's violent behavior like yelling and physical punishment is included in one of the parenting patterns which is called authoritarian. Parenting is one of the factors that influence temperament. Temperament is an individual difference in behavioral or characteristics responses that have existed since birth, but can change and develop along with  individual experience. This study aimed to determine the correlation of father's violent behavior to adolescents temperament. This research is quantitative research with a correlation method by using a cross sectional approach. The total population of this research was 596 people. The samples in this study consist of 145 respondents by using Stratified Random Sampling and simple random sampling techniques. The measuring instrument used a questionnaire. The analysis that used was bivariate analysis with chi-square statistical test. The results of this study showed that there was no significant correlation between father's violent behavior and adolescents temperament surgency p-value = 1000, effortful control p-value 0,083, negative affectivity p-value 0,370 and affiliativeness 0,550 > (α 0,05). From the results of the study it can be concluded that father's violent behavior has no influence on the adolescents temperament, this can be due to other factors that more strongly influence the temperament of adolescents such as the environment and peers. Parents are expected to provide good examples in adolescents with didn’t showing excessive anger and emotion because the environment will affect attitudes and behavior of a adolescents.Keywords: Adolescents, Father's Violence Behavior, Temperament